AccessPhysiotherapy. Issue 2 (3rd July 2021) - Stuart, Daniel
Abstract: AccessPhysiotherapy is a primary component of McGraw-Hill's suite of Access products. Under the umbrella of the publisher's broader network, it operates in conjunction with the wider interface of searchable e-book content, reference guidelines, and test prep materials. The collection caters to physical therapy practitioners and students, but remains relevant as an interdisciplinary resource for medical educators. Its e-books functions as the major component of the platform and may be accessed directly by way of a simple search query or browser component. One unique aspect of AccessPhysiotherapy is its integration with F.A. Davis Physical Therapy and Athletic Training collections. These special catalogs of reference books, physical therapy cases, and instructional videos are among the most comprehensive educational resources in the disciplines of physical therapy. Medical libraries can benefit from the AccessPhysiotherapy's integrated collection of e-books and broader content. Schools and departments within health sciences institutions will also find the content worthwhile.